Primary mediastinal B-cell lymphoma treated with CHOP-like chemotherapy with or without rituximab: results of the Mabthera International Trial Group study - Rieger, Martin; Österborg, A.; Pettengell, R.; White, D.; Gill, D.; Walewski, J.; Kuhnt, E.; Loeffler, M.; Pfreundschuh, M.; Ho, Anthony Dick (Annals of oncology, 2011)
Background - The aim of this subgroup analysis of the Mabthera International Trial Group study was to evaluate the impact of chemotherapy and rituximab in primary mediastinal B-cell lymphoma (PMBCL) in comparison to other diffuse large B-cell lymphoma (DLBCL). - Methods - Patients were randomly assigned to six cycles of CHOP-like regimens with or without rituximab. - Results - Of 824 patients enrolled, 87 had PMBCL and 627 other types of DLBCL. Rituximab increased the rates of complete remission (unconfirmed) in both PMBCL (from 54% to 80%, P = 0.015) and DLBCL (from 72% to 87%, P < 0.001). In PMBCL, rituximab virtually eliminated progressive disease (PD) (2.5% versus 24%, P < 0.001), whereas without rituximab, PD was more frequent in PMBCL than in DLBCL (24% versus 10%, P = 0.010). With a median observation time of 34 months, 3-year event-free survival (EFS) was improved by rituximab for PMBCL (78% versus 52%, P = 0.012) and for DLBCL (81% versus 61%, P < 0.001). Overall survival benefit was similar for DLBCL (93% versus 85%, P < 0.001) and PMBCL (89% versus 78%, P = 0.158). - Conclusion - In young patients with PMBCL (age-adjusted International Prognostic Index 0-1), rituximab added to six cycles of CHOP-like chemotherapy increases response rate and EFS to the same extent as other DLBCL. The combination of rituximab with CHOP chemotherapy is an effective treatment in PMBCL with good prognosis features.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.09.2022